2019
DOI: 10.1111/mcn.12769
|View full text |Cite
|
Sign up to set email alerts
|

“A child may be tall but stunted.” Meanings attached to childhood height in Tanzania

Abstract: Stunting affects large numbers of under‐fives in Tanzania. But do caretakers of under‐fives recognize height as a marker of child growth? What meanings do they attach to linear growth? An ethnographic study using cultural schemas theory was conducted in a rural community in Southeastern Tanzania to investigate caregivers' conceptualizations of child height in relation to growth and the meanings attached to short stature. Data for the study were collected through 19 focus group discussions, 30 in‐depth intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Additionally, neighbors, drug store attendants, community health workers, and professional health workers played vital roles in facilitating mothers’ ability to ensure access to and utilization of medical care for their children. The caregivers’ reported reliance on small drug shops and CHWs for accessing medical care for themselves and their children is alarming, as (i) the CHWs are not professional health care providers, and (ii) the drug shops in the community are operated by unqualified attendants who offer a variety of medications, mostly without prescription [ 24 ]. The practice of relying on these workers may fuel self-medication practices, which have many adverse effects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, neighbors, drug store attendants, community health workers, and professional health workers played vital roles in facilitating mothers’ ability to ensure access to and utilization of medical care for their children. The caregivers’ reported reliance on small drug shops and CHWs for accessing medical care for themselves and their children is alarming, as (i) the CHWs are not professional health care providers, and (ii) the drug shops in the community are operated by unqualified attendants who offer a variety of medications, mostly without prescription [ 24 ]. The practice of relying on these workers may fuel self-medication practices, which have many adverse effects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fieldwork setting of this research has been described elsewhere [ 24 ], but, in short, Morogoro region is considered one of Tanzania’s “food baskets”—i.e., high food-producing regions—but has a relatively high prevalence of stunting (33%) among under-five children [ 4 ]. The rural location of Kilosa District, which has a high prevalence of infant malnutrition and anemia in a context of plenty, make it an appealing choice for examining the capabilities that contribute to healthy child growth.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in the concepts regarding growth and height in the accounts of the local people in this study and in the biomedical model are consistent with those found in previous research conducted in Guatemala [22] and in rural Mexico [15]. The lack of a concept of height within the framework of growth of most of the participants of the current study seems to emanate from their cultural schemas on the origin of height, as they appear to view a child’s stature as the result of God’s will (Mpango wa Mungu ) or as function of heredity (For more information, see [31]. This schema is indicative of a failure to recognize nutritional stunting among the caregivers in the study setting, which is of great concern given the high prevalence of childhood stunting in the country [1,3].…”
Section: Discussionmentioning
confidence: 47%
“…The lack of a concept of height in the framework of growth described by most participants seemed to emanate from their beliefs about the origin of their child’s height, with many saying they feel they have no control over their child’s stature. Although some of the participants indicated they are aware that having a good diet has a positive impact on growth, most said they believe a child’s stature is mainly determined by God’s will or heredity (more details presented in [31]. ).…”
Section: Resultsmentioning
confidence: 99%
“…This paper is embedded into larger research on multi-dimensional child growth [ 12 , 13 , 25 ] using the Capability Framework for Child Growth as a conceptual model. The concept of multi-dimensional child growth is modeled based on Sen and Nussbaum’s work on the capability approach [ 9 , 11 , 26 ].…”
Section: Methodsmentioning
confidence: 99%